Inventory Accounting Practices and Their Role in Financial Performance Evaluation: Praktik Akuntansi Persediaan dan Perannya dalam Evaluasi Kinerja Keuangan - Nestariya, Handar; Rahayu, Duwi (Indonesian Journal of Law and Economics Review, 2024)
Inventory is a crucial asset for businesses, directly affecting their financial performance. However, despite its significance, many businesses struggle to implement inventory accounting practices in line with established standards. This study addresses the knowledge gap concerning the application of inventory accounting according to PSAK 14, focusing on Central Development Stores. The research employs a descriptive qualitative approach, gathering both primary and secondary data through interviews, documentation, and literature study. The findings reveal that the store employs a periodic physical inventory system and utilizes the FIFO (First In First Out) method for inventory valuation. The analysis indicates a partial compliance with PSAK 14, with a checklist percentage of 60%, highlighting areas for improvement. A notable discovery is that the store has not yet prepared financial statements, which could significantly impact its financial management practices. The novelty of this research lies in its practical evaluation of the implementation of PSAK 14 within a real business context, offering insights into common challenges. Implications suggest the necessity for the store to enhance its accounting practices to fully comply with PSAK 14, thus improving financial transparency and performance evaluation. Highlights: Partial Compliance: The store's accounting meets 60% of PSAK 14 requirements. Inventory Method: Uses Periodic system and FIFO for inventory valuation. Financial Reporting Gap: The store has not prepared financial statements yet. Keywords: Inventory, PSAK 14, Financial Performance, Inventory Valuation, Accounting Practices